Probing Different Approaches in Ultraviolet Radiation Personal Dosimetry - Ball Sports and Visiting Parks - Timo Heepenstrick; Claudine Strehl; Marc Wittlich (Frontiers Media S.A., 2022)
Solar ultraviolet radiation (UVR) continues to be a decisive influencing factor for skin health. Besides acute damage (e.g. erythema), chronic light damage is of particular relevance. Skin cancer can develop on the basis of this light damage. Knowledge about irradiation is crucial for the choice of preventive measures, but has so far been incomplete in many occupational and leisure activities. Often a methodological problem in study design is the cause. Here we report on the clarification of two issues. First, further values are to be determined on the way to a comprehensive exposure register of leisure-related activities. Furthermore, it is to be determined to what extent the measurement setting can have an influence on the measurement campaigns. For long-term measurements, football referees were equipped with dosimeters over several months, selective measurements during visits to parks were carried out by on-site recruitment of test persons. It turned out that the choice of method also depends on the expected compliance of the test persons. Long-term measurements of specific activities such as playing football are particularly suitable for observing the course of UV exposure over the year and generating resilient mean values. Point measurements such as visits to parks can also do this if there are enough such events spread over the year. However, they are particularly suitable for such on-site campaigns, as they may be combined with awareness campaigns of the issue of skin cancer. They also allow many measurements to be taken at the same time in one place. Both playing football and visiting parks are associated with high levels of radiation, so specific prevention concepts need to be developed. We were able to determine that the sunburn dose for light skin types was reached or exceeded for both of the investigated activities.